2013
DOI: 10.3892/or.2013.2632
|View full text |Cite
|
Sign up to set email alerts
|

An osteopontin promoter polymorphism is associated with aggressiveness in breast cancer

Abstract: Abstract. Metastasis-related genes are deregulated in cancer by aberrant expression or splicing. Here, we analyzed polymorphic sites in the osteopontin promoter as potential contributors to aberrant expression in breast cancers. This study comprised 241 breast cancer specimens, for which DNA from normal surrounding tissue was available for 111, and 65 healthy breast samples. The polymorphic site in position -443 of the promoter was associated with tumor grade. As expected, there was no association between prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…A detailed study of 241 breast cancer specimens in comparison with DNA from surrounding normal tissue as well as healthy breast samples revealed that the polymorphic site in position −443 of the promoter was associated with tumor grade. This very site, but not others (at −1748 or −1776), showed differences between ER-positive and ER-negative breast cancers and between PR-positive and PR-negative breast cancers, indicating that the SPP1 promoter SNPs −443 (rs11730582) and −1748 (rs2728127) are important for breast cancer aggressiveness (Ramchandani and Weber, 2013). Melanoma metastases that were homozygous for the −443C allele expressed significantly higher levels of SPP1 mRNA compared with those that were either heterozygous (−443T/C) or homozygous for the −443T allele.…”
Section: Regulation Of Opnmentioning
confidence: 93%
“…A detailed study of 241 breast cancer specimens in comparison with DNA from surrounding normal tissue as well as healthy breast samples revealed that the polymorphic site in position −443 of the promoter was associated with tumor grade. This very site, but not others (at −1748 or −1776), showed differences between ER-positive and ER-negative breast cancers and between PR-positive and PR-negative breast cancers, indicating that the SPP1 promoter SNPs −443 (rs11730582) and −1748 (rs2728127) are important for breast cancer aggressiveness (Ramchandani and Weber, 2013). Melanoma metastases that were homozygous for the −443C allele expressed significantly higher levels of SPP1 mRNA compared with those that were either heterozygous (−443T/C) or homozygous for the −443T allele.…”
Section: Regulation Of Opnmentioning
confidence: 93%
“…iOPN was found in dendritic cells [7375], macrophages [76], and nerve cells [77]. Indeed, iOPN localizes to the nucleus of 293 cells where it mediates cell duplication through association with polo-like kinase 1 [54], whereas in fibroblasts, iOPN plays a role in cell migration [78]. Moreover, deficient expression of iOPN in natural killer (NK) cells causes impaired expansion and increased apoptosis of these cells following stimulation with IL-15, resulting in defective immune response to viral infection and tumor cells [79].…”
Section: Opn General Featuresmentioning
confidence: 99%
“…In addition, a number of studies have demonstrated that OPN promoted tumor invasion and metastasis and regulated MMP-9 secretion (27)(28)(29)(30)(31). OPN was shown to combine with integrin αvβ3 and activate NF-κB (nuclear factor-κB) through the PI3K/Akt/IKK (κB kinase inhibitor) signaling pathway, increasing the secretion of urokinase-type plasmi nogen activator A (uPA) and promoting tumor invasion (32,33).…”
Section: Discussionmentioning
confidence: 99%